Biometry of Hard Palate on Digital Photographs: A Methodology for Quantitative Measurements - Saviolo Moreira,Rafael (Sociedad Chilena de Anatomía, 2006)
The objective of this paper is to establish, validate and test the reproducibility and accuracy of a digital method to measure linear and angular distances in human hard palate of dry skulls. Digital photographs were made in 10 human adult skulls and measurements were made with the aid of AutoCAD software and with a digital caliper in the same skulls by one observer in a blind fashion to compare both methods. To validate the digital method, measurements was made in 20 skulls by 3 observers. The differences of the measurements were not statistically significant between both method and between the 3 observers. The use of digital cameras followed by image analysis with AutoCAD, a software initially developed for engineering and architecture, revealed to be an excellent tool for biometry in morphology in medical and dentistry areas combining easy handling with accessibility